MINORITY SHAREHOLDERS IN MALAYSIA: IS THEIR RIGHT PROTECTED? - Suraiya Ishak; Ahmad Raflis Che Omar (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2010)
Issues on corporate governance can be deliberate from various dimensions. This study explores the issue of governance related to the minority shareholders’ in Malaysia. The objective of this study is to describe the protection pertaining to the right of minority shareholders’ group through shareholder activism in Malaysia. This study employs a case study technique on two corporate cases selected from banking industry for the year 2008 and 2010. The observation emphasizes on shareholder activism initiated by the Minority Shareholder Watchdog Group (MSWG). It is summarizes that retail and dispersed shareholders in Malaysia are moving towards an improved level of rights’ protection due to shareholder activism. As far as the minority’s right is concern, further improvement is needed to strengthen current legislation framework despite the existence of shareholder activism by MSWG